2016
DOI: 10.2147/dddt.s101449
|View full text |Cite
|
Sign up to set email alerts
|

A novel imidazopyridine derivative, X22, attenuates sepsis-induced lung and liver injury by inhibiting the inflammatory response in vitro and in vivo

Abstract: Sepsis remains a leading cause of death worldwide. Despite years of extensive research, effective drugs to treat sepsis in the clinic are lacking. In this study, we found a novel imidazopyridine derivative, X22, which has powerful anti-inflammatory activity. X22 dose-dependently inhibited lipopolysaccharide (LPS)-induced proinflammatory cytokine production in mouse primary peritoneal macrophages and RAW 264.7 macrophages. X22 also downregulated the LPS-induced proinflammatory gene expression in vitro. In vivo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Pro-inflammatory cytokines, such as TNF-α and IL-6, are primarily involved in the promotion of inflammatory processes and have an important role in liver injury ( 20 ). Cytokine profile analysis confirmed that both IL-6 and IL-10 became significantly elevated ( p < 0.05) during the early viral replication phase and then gradually declined into the normal range as viral RNA became undetectable ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines, such as TNF-α and IL-6, are primarily involved in the promotion of inflammatory processes and have an important role in liver injury ( 20 ). Cytokine profile analysis confirmed that both IL-6 and IL-10 became significantly elevated ( p < 0.05) during the early viral replication phase and then gradually declined into the normal range as viral RNA became undetectable ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Histological sections were reassessed by one board-certified pathologist who was blinded to the animal groups. To evaluate cholangitis in the liver, the grade of cholangitis was scored as described before 16,17 .…”
Section: Methodsmentioning
confidence: 99%
“…Sepsis is a serious systemic inflammatory response syndrome caused by a dy sregulated response to infection and the process is complex [1, 2]. Sepsis can result in multiple or gan failure and shock, including ca rdiac dysfunction, brain injury, lung damage and liver injury [3, 4, 5]. The high mortality and morbidity rates of sepsis has continued to rise [6].…”
Section: Introductionmentioning
confidence: 99%